Is TURBT able to cure high risk recurrent superficial or muscle invasive bladder cancer: Factors resulting in pT0 radical cystectomy specimens - Evangelos Mazaris (International Brazilian Journal of Urology, 2013)
Purpose In 76% of radical cystectomy patients there is discrepancy between the initial stage at transurethral resection and the final pathological stage of the cystectomy specimen. More specifically in contemporary series the absence of tumor at radical cystectomy specimens (stage pT0) is estimated at 5-25%. Our aim was to determine which factors contributed to the absence of tumor in our series of radical cystectomy patients. Materials and Methods Fifty one patients were submitted to radical cystectomy in our department over the last 10 years (January 2002-January 2012). A thorough analysis of the patients' files with no residual tumor on the cystectomy specimen (pT0) was performed. Possible factors contributing to such a result were described and a systematic analysis of the relevant literature was performed. Results Five patients had a pT0 stage after radical cystectomy. Four of them had transitional cell carcinoma and one of them had squamous cell carcinoma of the bladder on the initial transurethral resection. None of the tumors presented lymphovascular invasion. Four patients are still alive and one died 45 months postoperatively from a cardiac cause. Conclusions Four factors were identified in our study to contribute towards a pT0 cystectomy result. Those included the absence of lymphovascular invasion, the completeness of transurethral resection, the experience of the surgeon and the use of a standardized technique for the transurethral resection. The time to cystectomy in our series did not have a negative effect on pT0 final pathology result.